Compactação de um latossolo vermelho escuro sob sistema plantio direto e rendimento de grãos de trigo, soja e milho - Bonini, Andréia Kusumota (2006)
The objective of this study was to evaluate the effects of compactation level on soil physicals attributes: bulk density, macroporosity, microporosity and total porosity. Too evaluated the soil penetration resistence, infiltration rate, growth plants and grain yield of the cultures of wheat, soybean and corn, in Oxisol. The experiment was realized in Experimental Center of Agricultural Engineer, located in Cascavel (PR), Brazil. The experiment was fractirred in two phases. In 1th phase was installed in the experimental units (10 X 50 m) treatments four with compactation levels that were: T1= one wheel, T3= tree wheels, T5= five wheels e T0 = without additional compactation with compact roll. Evalueted the physical atributes, infiltration rate, growth plants and grain yield wheat. The 2th phase have iniciated after harvest of weath culture com posterior samples collection of soil to evalueted soil physicals attributes, soil penetration resistence before planter and after of the harvest of soybean and corn, growth plant and grain yield of soybean and corn. Soils samples indeform were coleted in the deeph 0,01; 0,1-0,2 e 0,2-0,3 m for analyses of soil bulk density and soil porosity, with five samples randomized in each treatment. The infiltration rate was evaluated by infiltrometer ring. The soil penetration resistence was evalueted electronic by penetrometer. The initial population and end population were avaliation by middle graduated rule. The grain yield coleted 5 samples radomized of each treatment, with useful area of 4.08, 6.15 e 14.25 m2, wheat, soybean and corn, respective. With results observed that the compaction levels installed in 1ª phase changed values bulk density and macroporosity, been evidence in deeph 0,0-0,1 m. The soil infiltration rate reduced significant with the increase of compaction levels. The grain yield wheat no were reduced. The grains yield of weath no was reduced with levels compactation. The values more increase of soil penetration resistence occured in treatments T3 and T5 in the layer 0,07-0,12 m. Ago effects of the shaft furrowing mecanism of the seedrills in reduced bulk density and macroporosity increase in deeph 0,0-0,1 m.